(untitled) (Editora Impacto Científico, 2025)
This study aims to provide information to foster discussion and reflection on education in a neoliberal environment, which, by transforming education into a commodity, has opened the door to privatization. This privatization is experiencing accelerated growth, which, in turn, has rapidly reduced teacher health. The research is qualitative in nature, utilizing bibliographic and documentary analysis. Sources consulted included websites of governmental news agencies and unions, as well as news sites outside of the mainstream media that are not solely guided by hegemonic interests. The theoretical review was exploratory, examining scientific bibliographic material to locate and identify prior studies on the chosen topic. For theoretical and methodological reasons, this article is divided into four parts. The first addresses education within the neoliberal context, followed by a discussion on the privatization of education. The third presents discussions regarding teacher health in the context described, and the fourth and final part offers suggestions to improve teacher health and well-being. The article concludes with the final remarks. DOI: https://doi.org/10.56238/edimpacto2025.092-004